The Role of Legal Language in Formulating Written Legal Rules in Indonesia - Jaya Mulya; Diky Dikrurahman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Legal language is a regulatory language intended to create justice and order in society, and is expected to protect personal interests and public interest. Because the legal language is modern Indonesian, the use of Indonesian must be clear, fixed, monosemantic and in accordance with the aesthetic requirements of the Indonesian language. Thus, to understand the rules of law and legal language, in principle, they are one unit in a legal discipline. If you want to learn and understand the rule of law, you must use good legal language. Legal rules are composed of a systematic legal language. From this point of view it is very clear, the role of legal language is very important to formulate legal rules in society. The problem is how are the rules of legal language used in formulating written legal rules in Indonesia? This study aims to determine the role of legal language in formulating written legal rules in Indonesia. While the type of research is normative legal research, namely legal research conducted by examining library materials, or secondary data or library research. And the results of the first research; rules of legal language to formulate written legal rules (1) Luges and exact; (2) Objective; (3) Careful definition; (4) Not emotional; (5) the exposure is conventional; (6) Not dogmatic (7) thrifty; (8) The form of the meaning is stable. Second; form of legal language; (1) The form of the word must be correct; (2) The meaning of the word must be precise; (3) Sentences must be clear; (4) Distinctive terms; (5) Not greeting people; (6) Typical wearing style; (7) The writing follows the EYD and (8) The legal norms are conveyed through sentences.